The Perspectives of Imam An-Nawawi and Imam Ibn al-Hummam on the Purity of Floors Cleansed with a Cloth from Cat Impurities: A Case Study of Medan Pet Cafe - Winata, Muhammad Fadli; Marpaung , Aripin (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
It is crucial for Muslims to understand and correctly implement the purification of impurities (najis) in all places, particularly on floors in public spaces, where some are merely mopped with a cloth. In this regard, there is a difference of opinion between Imam An-Nawawi and Imam Ibn al-Hummam regarding the purity of floors that have been mopped with a cloth. This study aims to examine the differing perspectives of Imam Ibn al-Hummam and Imam An-Nawawi on the purification of floors from impurities when cleaned using a mop or cloth. The research employs a normative sociological method with a comparative approach, incorporating field studies and a literature review of relevant references. The findings reveal that Medan Pet Cafe adopts a cleaning method for floors contaminated with cat waste by wiping the affected area with tissue, mopping it with a cloth, and spraying disinfectant. This procedure serves as the standard cleaning protocol in the establishment to ensure hygiene and comfort for visitors. From a fiqh perspective, there is a divergence in opinion between Imam An-Nawawi and Imam Ibn al-Hummam concerning the purification of floors contaminated by impurities. Imam An-Nawawi asserts that if an impurity comes into contact with a shaqil object (a heavy and solid object, in this case, the floor), the floor cannot be purified merely by wiping or mopping; rather, it must be washed with water to ensure complete purification from impurities. Conversely, Imam Ibn al-Hummam argues that simply wiping the floor is sufficient, as floors are shaqil objects that do not absorb impurities, thereby eliminating the necessity of water washing [Sangat penting bagi umat Islam untuk memahami dan mengerti bagaimana cara mensucikan najis dengan benar di semua tempat, terkhusus lantai di tempat umum, beberapa ada yang dipel dengan kain pel saja. Dalam hal ini, terdapat perbedaan pandangan antara Imam An-Nawawi dan Imam Ibnu Al-Hummam mengenai kesucian lantai yang dipel dengan kain. Penelitian ini bertujuan untuk mengkaji perbedaan pandangan Imam Ibnu al-Hummam dan Imam An-Nawawi mengenai kesucian lantai dari najis yang dipel dengan kain. Metode penelitian ini adalah sosiologis normatif yang bersifat komparatif, melakukan penelitian lapangan serta melakukan analisis pustaka terhadap referensi yang relevan dengan penelitian ini. Hasil penelitian menunjukkan penelitian ini menemukan bahwa metode yang digunakan oleh Medan Pet Cafe dalam mensucikan lantai yang terkena kotoran kucing adalah dengan mengusapnya menggunakan tisu, kemudian mengepelnya dengan kain, dan menyemprotkan cairan disinfektan. Prosedur ini menjadi standar pembersihan di tempat tersebut untuk memastikan kebersihan dan kenyamanan bagi pengunjung. Dari perspektif fikih, terdapat perbedaan pandangan antara Imam An-Nawawi dan Imam Ibnu Al-Hummam terkait kesucian lantai yang terkena najis. Imam An-Nawawi berpendapat bahwa apabila najis mengenai benda yang shaqil (benda berat dan padat, dalam hal ini lantai), maka lantai tidak dapat menjadi suci hanya dengan diusap atau dipel, melainkan harus disiram dengan air agar benar-benar terbebas dari najis. Sebaliknya, Imam Ibnu Al-Hummam berpendapat bahwa lantai cukup dibersihkan dengan cara diusap saja, karena lantai termasuk benda yang shaqil yang tidak menyerap najis, sehingga tidak memerlukan penyiraman air].